FPGA based Multichannel Bit Error Rate Tester for Spacecraft Data Acquisition System - Manoj Kumar A; R V Nadagouda; R Jegan (International Journal of Reconfigurable and Embedded Systems (IJRES), 2014)
Bit Error Rate (BER) is a principle measure of data transmission link performance. BER tester (BERT) consists of a Pattern Generator and an Analyzer that can be set to the same pattern. The payload data transmitted from the spacecraft consists of one, two or three channels per carrier based on the modulation scheme. The traditional equipments can do BER analysis for only one channel at a time. In order to support multichannel BER analysis, a Personal Computer (PC) based system is designed and implemented in Altera Stratix II (EP2S130F1508C5N) FPGA. Ethernet is configured using WIZnet 5300 (Ethernet Controller) and it is used for communication between FPGA and PC with an application. Application is used to transmit the Pattern Generator’s configurations from PC to FPGA and to receive Analyzer’s status. Packet processing is done for this communication using User Datagram protocol (UDP). On the whole, traditional equipments are replaced by the designed and implemented bit error rate tester.